Methane from organic waste - Capacillo, Albert (College of Engineering, 1965)
Capacity: 46,190 lbs/year -- Fixed capital investment: 825,551 -- Operating cost at maximum production: 165,400 -- Sales at maximum production: 480,000 -- Pay-off time: 2.18 years -- Break-even point: 40% capacity -- Shut-down point: 12.7% capacity